Trouble and transformation in higher education: identifying threshold concepts through faculty narratives about teaching writing. Issue 9 (1st September 2020) - Basgier, Christopher; Simpson, Amber
ABSTRACT: The theory of threshold concepts has given faculty a powerful way to name foundational, but difficult, disciplinary concepts. However, there is no methodological consensus about the best ways to identify them. In this article, we introduce a phenomenographically-derived narrative framework for identifying stages of threshold concept acquisition. We developed this framework through a study of faculty's conceptions of the teaching of writing situated within the normal course of disciplinary education across fields. Because of this focus, our framework has immediate application for anyone who wants to understand faculty members' thinking about the teaching of writing and help them acquire conceptions that support good pedagogy. More broadly, disciplinary faculty and researchers across higher education can use our narrative framework to identify their own or students' stages of threshold acquisition in a range of disciplines, and so adjust curricula accordingly.